2002
DOI: 10.1001/archpsyc.59.11.1053
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Impairments in Nonpsychotic Parents of Children With Schizophrenia and Attention-Deficit/Hyperactivity Disorder

Abstract: The aggregation of neurocognitive impairments in the parents of COS probands provides further evidence of etiologic continuity between COS and AOS. A substantial subgroup of parents of COS probands had a worse neurocognitive performance than that of any of the parents of ADHD and CC probands. Receiver operating characteristic curves showed that when rigorous cutoffs define neurocognitive impairments, the combination of scores on certain neurocognitive tasks produced a level of diagnostic accuracy in the parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 52 publications
2
45
1
Order By: Relevance
“…The data suggest that neuromotor, language and verbal memory dysfunctions [20][21][22] as well as some subtle selfperceived cognitive-affective discomforts are increased in SSchP. This finding further confirms previous reports [8,9] on BS in unaffected first-degree relatives of schizophrenics (which differed from controls in the same, but a less marked way as schizophrenics did [8,9]), allowing the sketching out of BSABS subsyndrome patterns across the samples.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The data suggest that neuromotor, language and verbal memory dysfunctions [20][21][22] as well as some subtle selfperceived cognitive-affective discomforts are increased in SSchP. This finding further confirms previous reports [8,9] on BS in unaffected first-degree relatives of schizophrenics (which differed from controls in the same, but a less marked way as schizophrenics did [8,9]), allowing the sketching out of BSABS subsyndrome patterns across the samples.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, BS are likely to identify subtle expressions of genetic liability to schizophrenia (as well as the neuromotor and neurocognitive abnormalities that aggregate in the nonpsychotic first-degree relatives [10,11,[20][21][22]) subjectively perceived as unelaborated, yet discomforting, interferences in daily experience [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairments seem to be genetically linked to schizophrenia since non-psychotic parents of childhood-onset schizophrenic patients performed worse in neurocognitive tasks than parents of ADHD children (Asarnow et al, 2002) and relatives of schizophrenic patients revealed a higher percentage of ADHD symptoms (31%; especially higher scores on magical ideation, perceptual aberration and more neurological impairments) than relatives of healthy controls (Keshavan et al, 2003).…”
Section: Comorbid Associations Of Schizophrenia and Adhd?mentioning
confidence: 99%
“…Of note, some studies have suggested a link between childhood-onset ADHD and schizophrenia but the nature of this remains unclear (Asarnow et al, 2002;Subotnik et al, 2005). That said, adults with ADHD show a range of psychosocial deficits, which partially overlap with deficits seen in schizophrenia.…”
mentioning
confidence: 99%